The Roles of Corticotropin-Releasing Factor-Related Peptides and Their Receptors in the Cardiovascular System - Nazarloo, Hossein P.; Buttrick, P. M.; Saadat, H.; Dunn, A. J. (Current Protein and Peptide Science, 2006)
Corticotropin-releasing factor (CRF), CRF-related peptides and their receptors are present in the central nervous system and in peripheral tissues including the immune, reproductive and cardiovascular systems. CRF and urocortin (urocortin 1) bind to the CRF receptor type 1 (CRF1 receptor) and the CRF receptor type 2 (CRF2 receptor), whereas urocortin 2 (formerly known as stresscopin related peptide) and urocortin 3 (formerly known as stresscopin) bind with high affinity to the CRF2 receptor. Recent studies show that urocortin 1, urocortin 2 and urocortin 3 are potent regulators of cardiovascular function. This review highlights the role of cardiovascular CRF and related peptides and its relevance in mediating the adaptive response of the cardiovascular system to stressful conditions.
Keywords: urocortin